The CRISPR-Cas9 crATIC HeLa transcriptome: Characterization of a novel cellular model of ATIC deficiency and ZMP accumulation - Mazzarino, Randall C; Baresova, Veronika; Zikánová, Marie; Duval, Nathan; Wilkinson, Terry G; Patterson, David; Vacano, Guido N (Molecular genetics and metabolism reports, 2020)
In de novo purine biosynthesis (DNPS), 5-aminoimidazole-4-carboxamide ribonucleotide formyltransferase (EC 2.1.2.3)/inosine monophosphate cyclohydrolase (EC 3.5.4.10) (ATIC) catalyzes the last two reactions of the pathway: conversion of 5-aminoimidazole-4-carboxamide ribonucleotide [aka Z-nucleotide monophosphate (ZMP)] to 5-formamido-4-imidazolecarboxamide ribonucleotide (FAICAR) then to inosine monophosphate (IMP). Mutations in ATIC cause an untreatable and devastating inborn error of metabolism in humans. ZMP is an adenosine monophosphate (AMP) mimetic and a known activator of AMP-activated protein kinase (AMPK). Recently, a HeLa cell line null mutant for ATIC was constructed via CRISPR-Cas9 mutagenesis. This mutant, crATIC, accumulates ZMP during purine starvation. Given that the mutant can accumulate ZMP in the absence of treatment with exogenous compounds, crATIC is likely an important cellular model of DNPS inactivation and ZMP accumulation. In the current study, we characterize the crATIC transcriptome versus the HeLa transcriptome in purine-supplemented and purine-depleted growth conditions. We report and discuss transcriptome changes with particular relevance to Alzheimer's disease and in genes relevant to lipid and fatty acid synthesis, neurodevelopment, embryogenesis, cell cycle maintenance and progression, extracellular matrix, immune function, TGFβ and other cellular processes.
Keywords: xanthine monophosphate, (XMP); cyclooxygenase, (COX); minus adenine crATIC to minus adenine WT comparison, (MM); fetal calf macroserum, (FCM); adenosine monophosphate, (AMP); differentially expressed gene, (DEG); AMP-activated protein kinase, (AMPK); cytosolic phospholipase A2, (cPLA2); RNA-seq; cytochrome, P450 (CYP); adenylosuccinate lyase, (ADSL); Development; mammalian Target of Rapamycin, (mTOR); interferon, (INF); adenine phosphoribosyltransferase, (APRT); Tuberous Sclerosis Complex 1 and 2, (TSC1 and TSC2); 5-aminoimidazole-4-carboxamide ribonucleotide, (ZMP); phosphoribosylaminoimidazole carboxylase/phosphoribosylaminoimidazole succinocarboxamide synthetase, (PAICS); fatty acid amide hydrolase, (FAAH); 5-aminoimidazole-4-carboxamide ribonucleotide formyltransferase/inosine monophosphate cyclohydrolase, (ATIC); fetal calf serum, (FCS); adenosine triphosphate, (ATP); plus adenine crATIC to plus adenine WT comparison, (PP); guanosine monophosphate, (GMP); 5-aminoimidazole-4-carboxamide ribonucleoside, (AICAr); false discovery rate, (FDR); arachidonic acid, (AA); gene ontology, (GO); inosine monophosphate, (IMP); lipoxygenase, (LOX); Purine synthesis; Alzheimer's disease; fragments per kilobase of exon per million reads mapped, (FPKM); phospholipase, (PLA); phosphoribosyl pyrophosphate, (PRPP); de novo purine synthesis, (DNPS); AICA-ribosiduria; 5-formamido-4-imidazolecarboxamide ribonucleotide, (FAICAR)